Antibiotic therapy in the critically ill - expert opinion of the Intensive Care Medicine Scientific Subcommittee of the European Society of Anaesthesiology. Issue 4 (April 2017) - Martin-Loeches, Ignacio; Leone, Marc; Madách, Krisztina; Martin, Claude; Einav, Sharon
Abstract : Antimicrobial treatment is the cornerstone of infection treatment, and the selection of appropriate antibiotic treatment for critically ill patients is challenging. Clinicians working with critically ill patients usually feel a greater obligation towards their patient than towards maintenance of the delicate ecological balance of prevalent microbiological threats and their resistance patterns. Although antibiotic overtreatment is a frequent phenomenon, patient outcomes need not be compromised when antibiotic treatment is driven by informed decision-making. At the 2016 Euro Anaesthesia Conference (London, UK), the European Society of Anaesthesia Intensive Care Scientific Subcommittee convened an expert panel on antibiotic therapy. This article summarises the main conclusions of the panel, namely the principles of antibiotic therapy that all physicians working with critically ill patients must know.